2009
DOI: 10.1002/cbdv.200800097
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol Glycosides from Lobularia maritima and Their Potential Role in Plant Interactions

Abstract: Six kaempferol glycosides, four of them characterized for the first time, were isolated from the leaf extract of Lobularia maritima. The structural elucidation was performed by a combined approach using Electrospray-Ionization Triple-Quadrupole Mass-Spectrometric (ESI/TQ/MS) techniques, and 1D- and 2D-NMR experiments (1H, 13C, DEPT, DQ-COSY, TOCSY, ROESY, NOESY, HSQC, HMBC, and HSQC-TOCSY). The isolated kaempferol derivatives have different disaccharide substituents at C(3) and four of them have a rhamnose uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…The present study reported the phytotoxic activity of the fractions from which juglanin and avicularin were isolated, corroborating other studies that reporting this activity (Berrehal et al, 2010;Rodrigues et al, 2010;Fiorentino et al, 2009;Esposito et al, 2008;Melos et al, 2007). Therefore, the species Myrcia tomentosa should be of interest in studies on the development and production of natural herbicides.…”
Section: Chemical Fractionation and Purificationsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study reported the phytotoxic activity of the fractions from which juglanin and avicularin were isolated, corroborating other studies that reporting this activity (Berrehal et al, 2010;Rodrigues et al, 2010;Fiorentino et al, 2009;Esposito et al, 2008;Melos et al, 2007). Therefore, the species Myrcia tomentosa should be of interest in studies on the development and production of natural herbicides.…”
Section: Chemical Fractionation and Purificationsupporting
confidence: 91%
“…The products F8 CI and F9 EI were pure substances and were subjected to 1 H NMR and 13 C NMR. The NMR data for F8 CI and F9 EI coincide with those described in the literature for the compounds juglanin (Fiorentino et al, 2009) and avicularin (Kim et al, 1994), respectively (Fig. 5).…”
Section: Chemical Fractionation and Purificationsupporting
confidence: 85%
“…The structures of the known compounds (6e10, 12 and 15e24) were identified by means of spectroscopic analyses (ESIMS, 1 H and 13 C NMR) and by comparing the spectroscopic data with literature values of the following compounds: 3,5-di-C-b-D-glucopyranosyl phloroacetophenone (6) (Sato et al, 2004), kaempferol 3-robinobioside (7) (Brasseur and Angenot, 1986), kaempferol 3-Ob-D-glucopyranosyl (1 / 2)-a-D-xylopyranoside (8) (Fiorentino et al, 2009), icariside B 5 (9) (Matsunami et al, 2010), tamarixetin 3-robinobioside (10) (Barrero et al, 1998), leptonol (12) (Li and Zhu, 1998), 8-acetyl-7-hydroxy-5,6-dimethoxy-2,2-dimethyl-2H-l-benzopyran (15) (Kamperdick et al, 1997), evodione (16) (Kamperdick et al, 1997), leptene A (17) (Guo-Lin et al, 1997), isoevodionol (18) (Li and Zhu, 1999), 6-acetyl-7-hydroxy-5-methoxy-2,2-dimethyl-2H-chromene (19) (Donnelly et al, 1995), 6-(1-methoxyethyl)-5,7,8-trimethoxy-2,2-dimethyl-2H-l-benzopyran (20) (Kamperdick et al, 1997), acronyculatin G (21) (Kozaki et al, 2014), 6-(lhydroxyethyl)-5,7,8-trimethoxy-2,2-dimethyl-2H-1-benzopyran (22) (Kamperdick et al, 1997), 3,5,4 0 -trihydroxy-8,3 0 -dimethoxy-7-(3-methylbut-2-enyloxy)flavone (23) (Sultana et al, 1999), and 3,5,3 0 -trihydroxy-8,4 0 -dimethoxy-7-(3-methylbut-2-enyloxy) flavone (24) (Xie et al, 2011b).…”
Section: Resultsmentioning
confidence: 99%
“…No data have been found on its medicinal properties in other papers, except for the use against kidney stones in Sicily and in case of toothache (Barone, 1963) in Calabria. This plant contains kaempferol glycosides (Fiorentino et al, 2009) and its seeds are rich in cis-11-eicosenoic acid (Mikolajczak et al, 1963); some varieties can also synthesize acylated cyanidin 3-sambubioside-5-glucosides (Tatsuzawa et al, 2006) and respond to nickel and cadmium stress producing antioxidative enzymes (Schickler and Caspi, 1999).…”
Section: Discussionmentioning
confidence: 99%